Effective Factors to Manage Madrasah Teacher Work Productivity in the Disruption Era: An Analysis of Partial Correlation - Ulfah, Yetty Faridatul; Purwanto, Purwanto; Khuriyah, Khuriyah (Technium Social Sciences Journal, 2023)
This study aims to find out how factors both internal and external to teachers can affect how productive they are at work. This is accomplished by researching the effects of the following factors on teacher productivity: 1) transformational leadership of madrasa principals, 2) self-efficacy, 3) organizational citizenship behavior, and 4) transformational leadership, self-efficacy, and behavior of organizational citizenship combined. This study used a quantitative model with a correlation approach. This study was carried out at three MTs N in the Sukoharjo Regency, Central Java, in 2022 using a sample of 126 madrasah instructors. The research sample method included proportionate stratified random sampling, and questionnaires were used to gather data for each variable under investigation. The Kolmogorov-Smirnov test, Product Moment correlation coefficient test, and Anova test were employed as data analysis tools. Correlation and partial correlation tests are used to test hypotheses. This study comes to the following conclusions: 1) The external element of madrasa principals' transformational leadership favorably and significantly affects teachers' job productivity with tcount of 0.616 higher than rtable of 0.1736, 2) internal factors of teacher self-efficacy positively and significantly affect teacher work productivity with a rcount of 0.604 higher than an rtable of 0.1736, 3) internal factors of teachers’ organizational behavior citizenship (OCB) positively and significantly influences teacher work productivity with a rcount of 0.468 higher than an rtable of 0.1736, and 4) transformational leadership, self-efficacy and OCB as a whole together have an influence on teacher work productivity with Fcount of 55.680 higher than Ftable of 0.1736 indicating that the contribution of those three factors on teacher work productivity is 57.8%, and 42.2% is influenced by other variables not analyzed in this study.